Deposition of Cl‐doped CdTe polycrystalline films by close‐spaced sublimation. Issue 6 (30th March 2015) - Okamoto, Tamotsu; Takahashi, Kohei; Akiba, Sho; Yasuda, Nao; Tokuda, Satoshi; Kishihara, Hiroyuki; Ichioka, Akina; Doki, Takahiro; Sato, Toshiyuki; Tsuboi, Nozomu; Wakita, Kazuki; Yamada, Akira; et al.
Abstract The effects of Cl‐doping on the CdTe layers by the close‐spaced sublimation (CSS) deposition were investigated. Cl‐doped CdTe polycrystalline films were deposited on graphite substrates by CSS method using a mixture of CdTe and CdCl2 powder as a source. In X‐ray diffraction (XRD) patterns of the obtained films with various deposition times, many diffraction peaks other than CdTe peaks were observed in the deposition times lower than 10 min. These diffraction peaks were probably due to the formation of chlorides of Cd, Te and C, such as CdCl2, TeCl4, Te3Cl2 and C10Cl8. X‐ray fluorescence (XRF) and secondary ion mass spectrometry (SIMS) analyses revealed that a large amount of chlorine was contained in the films with the deposition times lower than 10 min, and that Cl concentration decreased with increasing the deposition time above 3 min. These results indicate that the films containing the chlorides of Cd, Te and C in addition to CdTe are formed in the initial stage of the CSS deposition using a mixture of CdTe and CdCl2 powder as a source. Cross‐sectional images revealed that the grain size was decreased by the effect of Cl‐doping. Furthermore, current‐voltage (I ‐V) characteristics of the CdTe/graphite structures were measured, and it was found that the resistivity of the Cl‐doped CdTe layer was much higher than that of the undoped CdTe layer. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)